PENGARUH PROMOSI PENJUALAN TERHADAP MINAT KONSUMEN BISNIS KENDARAAN BERMOTOR PADA CV. CITRA HONDA NUSANTARA PEKANBARU - Apriwati Aritonang; Seno Andri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Along with economic growth and technological development, the business world was experiencing rapid growth with the emergence of companies that strive to create products and services to meet the needs and desires of consumers. Businesses initially have a large market share, as well as extensive marketing areas, are now required to work more efficiently and effectively and responsive anticipate that they will enter markets both at present and in the time to come. , To attract buyers, one attempts to do is to repair an effective marketing system. Effective marketing in the application not only how to increase sales volume but also observe the behavior of consumers and businesses to meet the desires of consumers through product improvement in line with expectations konsumen.Penelitian aims to determine the effect of sales promotions on consumer interest in the motor vehicle business cv. Honda Nusantara Citra Pekanbaru. Data obtained from questionnaires with respondents as many as 55 people further processed using descriptive statistics and then the data is presented in tabular format with the numbers and percentages for subsequent analysis results indicate that the implementation of the promotion have a good influence on consumer interest in CV. Honda Nusantara Citra Pekanbaru. Promotion is affected by consumer interest with a value of R Square of R = 0.403, meaning is that the contribution of variable influence to variable interest konsuemen sale amounted to 40.3%, while the remaining 59.7% is influenced by other factors such as customer perception, behavior consumers and others.Keywords: marketing, promotion, consumer interest